Understanding dynamic capabilities - Winter, Sidney G. (Strategic Management Journal, 2003)
Abstract Defining ordinary or ‘zero‐level’ capabilities as those that permit a firm to ‘make a living’ in the short term, one can define dynamic capabilities as those that operate to extend, modify or create ordinary capabilities. Logically, one can then proceed to elaborate a hierarchy of higher‐order capabilities. However, it is argued here that the strategic substance of capabilities involves patterning of activity, and that costly investments are typically required to create and sustain such patterning—for example, in product development. Firms can accomplish change without reliance on dynamic capability, by means here termed ‘ad hoc problem solving.’ Whether higher‐order capabilities are created or not depends on the costs and benefits of the investments relative to ad hoc problem solving, and so does the ‘level of the game’ at which strategic competition effectively occurs. Copyright © 2003 John Wiley & Sons, Ltd.